OVERVIEW STUDY ON MURRAYA KOENIGII (MITHA NEEM): RUTACEAE - Verma, Sunita (Journal of Drug Delivery and Therapeutics, 2018)
Murraya koenigii (Rutaceae) commonly known as â€œCurry leavesâ€ and â€œMeetha neemâ€. It is an important leafy vegetable. Its leaves are widely used in Indian cookery for flavouring foodstuffs. The leaves are used traditionally as spice. The aim of the present study is to information about classification, origin, morphological characters, traditionally use of Murraya koenigii by tribal community of Jhunjhunu District of Rajasthan in many cures of diseases. Keywords: Medicinal Plant, Traditionally, Antibacterial, Antioxidant